PELAKSANAAN PEMBINAAN NARAPIDANA DENGAN SISTEM PEMASYARAKATAN DI LAPAS KELAS IIB PARIAMAN - Muhammad Iqram; Herry Fernandes Butar Butar (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2022)
Abstract This study aims to examine how the implementation of guidance for convicts in the Penitentiary Class IIB Pariaman. The correctional system is no longer aimed at retribution and resocialization, however, it has the goal of social reintegration. This study uses a qualitative method by conducting a literature study. The author looks for data sourced from scientific works, such as books on coaching in prisons, and also from news stories in the media. From the data from various sources, it was found that the implementation of guidance in correctional institutions is regulated by PP 31 of 1999 concerning the Guidance and Guidance of Correctional Inmates. Where in the coaching consists of various stages where there is initial coaching in the form of admission and orientation, followed by advanced coaching such as assimilation and skills development and the final coaching stage with assimilation and integration. In fostering prisoners, they highly respect the dignity of prisoners as whole human beings, every prisoner's rights must be fulfilled and must not be arbitrary to them.